The relationship between website design and positive eWOM intention: testing mediator and moderator effect - Phan, Quyen Phu Thi; Pilík, Michal (Journal of Business Economics and Management, 2018)
Electronic word of mouth (eWOM) has paid attention to the phenomenon of marketing strategy because of the power of online comments to behavioural consequences. The key challenge for scholars and practitioners is to explore why consumers would like to give positive reviews of products and service. However, little empirical research has been conducted on the effect of website design on eWOM intention. The objective of this paper is to investigate the impact of website design (aesthetic and usability) on eWOM intention, which is based on the adoption of the stimulus – organism – response model. To test the hypotheses, the study uses the Partial Least Squares (PLS) to test a total of 290 respondents collected from Taiwanese customers via an online survey. The outcomes show the impact of the website’s design on the attitude toward it, which would lead to positive eWOM. The study also provides empirical evidence on the moderating role of online purchasing experience and the mediating effect of attitude toward a website on eWOM intention. Finally, the discussions also show implications and managerial insight for both scholars and marketers.